Impact of Adjuvant Chemotherapy on Variant Histology of Upper Tract Urothelial Carcinoma: A Propensity Score-Matched Cohort Analysis - Lo, Chi-Wen; Li, Wei-Ming; Ke, Hung-Lung; Chang, Yi-Huei; Wu, Hsi-Chin; Chen, I-Hsuan Alan; Lin, Jen-Tai; Huang, Chao-Yuan; Chen, Chung-Hsin; Tseng, Jen-Shu; Lin, Wun-Rong; Jiang, Yuan-Hong; et al. (Frontiers in Oncology, 2022)
Background The advantage of adjuvant chemotherapy for upper urinary tract urothelial cancer (UTUC) has been reported, whereas its impact on upper tract cancer with variant histology remains unclear. We aimed to answer the abovementioned question with our real-world data. Design, Setting, and Participants Patients who underwent radical nephroureterectomy (RNU) and were confirmed to have variant UTUC were retrospectively evaluated for eligibility of analysis. In the Taiwan UTUC Collaboration database, we identified 245 patients with variant UTUC among 3,109 patients with UTUC who underwent RNU after excluding patients with missing clinicopathological information. Intervention Those patients with variant UTUC were grouped based on their history of receiving adjuvant chemotherapy or not. Outcome Measurements and Statistical Analysis Propensity score matching was used to reduce the treatment assignment bias. Multivariable Cox regression model was used for the analysis of overall, cancer-specific, and disease-free survival. Results and Limitations For the patients with variant UTUC who underwent adjuvant chemotherapy compared with those without chemotherapy, survival benefit was identified in overall survival in univariate analysis (hazard ratio (HR), 0.527; 95% confidence interval (CI), 0.285–0.973; p = 0.041). In addition, in multivariate analysis, patients with adjuvant chemotherapy demonstrated significant survival benefits in cancer-specific survival (OS; HR, 0.454; CI, 0.208–0.988; p = 0.047), and disease-free survival (DFS; HR, 0.324; 95% CI, 0.155–0.677; (p = 0.003). The main limitations of the current study were its retrospective design and limited case number. Conclusions Adjuvant chemotherapy following RNU significantly improved cancer-related survivals in patients with UTUC with variant histology.